Measurement of Neighborhood Context in an Urban Cohort of HIV-Infected or at Risk Low-Income Women. Issue 1 (2nd January 2017) - Burke-Miller, Jane K.; Weber, Kathleen M.; Cohn, Susan E.; Hershow, Ronald C.; Sha, Beverly; French, Audrey L.; Cohen, Mardge H.
ABSRACT: The study of neighborhood disadvantage and health relies on census socioeconomic data but would benefit from reliable survey measures of factors that influence health within low income communities. The Perceptions of Neighborhood Environment Scale (PNES) was developed for use in the general U.S. population, and its measurement properties in a cohort of women who are low income and urban living with or at risk for HIV are described. The scale and all but one subscale have good psychometric and ecometric reliability, as well as convergent, construct, and concurrent validity, and are not collinear with household and community area income in low-income urban neighborhoods.